Occlusive vascular disease associated with cerebral arteriovenous malformations - Mawad, M.E. (1984)
Selective carotid angiography and computed tomography were used in a study of the association of occlusive vascular disease with cerebral arteriovenous malformations in 13 patients. The arterial occlusions ranged from focal stenosis in the major artery supplying the malformation to complete occlusion of the supraclinoid internal carotid artery with subsequent development of "moyamoya" collaterals. The majority of the arterial occlusions were proximal to the vascular malformation. Some, however, extended distal to the major branch supplying the arteriovenous malformation (AVM). Selective angiography with subtraction techniques defines the distinct angioarchitecture of these AVMs and the associated stenoses and collateral telangiectases.